An evaluation of the capability of data conversion of impression creep test - Cacciapuoti, B.; Sun, Wei; McCartney, D.G.; Morris, A.; Lockyer, S.; Ab Razak, N.; Davies, C.M.; Hulance, J. (Taylor & Francis, 2017)
High temperature power plant components are now working far beyond their operative designed life. Establishing their in-service material properties has become a matter of significant concern for power generation companies. Advantages for the assessment of creep material properties may come from miniature specimen creep testing techniques, like impression creep testing method, which can be treated as a quasistatic non-destructive technique and requires a small volume of material that can be scooped from in-service critical components, and can produce reliable secondary creep data. This paper presents an overview of impression creep testing method to highlight the capability in determining the minimum creep strain rate data by use of conversion relationships that relates uniaxial creep test data and impression creep test data. Stepped-load and stepped-temperature impression creep tests are also briefly described. Furthermore, the paper presents some new impression creep test data and their correlation with uniaxial data, obtained from P91, P92 and ½CrMoV steels at different stresses and temperatures. The presented data, in terms of creep strain rate against the reference uniaxial stress, are useful for calibration of impression creep testing technique and provide further comparative results for the evaluation of the reliability of the method in determining secondary creep properties.